Clima social familiar y logro de competencias en el área de comunicación de los estudiantes de cuarto grado de secundaria de las instituciones educativas públicas urbanas de Nauta 2022 - Piña Flores, Miguel Andres (2024)
The general objective of the study was to determine the relationship between the family social climate and the achievement of communication skills of fourth grade students in urban public institutions in Nauta 2022. The methodology used was relational research. The study design adopted was non-experimental and cross[1]sectional. The study had a population of 214 individuals, of which we worked with a stratified sample of 137 students. The survey technique was applied and the instrument used was the scale questionnaire for the communication competence achievement variable. It was concluded that there is an association between the variables family social climate and competence achievement in the area of communication of the students who participated in the research, according to the p-value=0.000